Mo의 급속열처리로 제조된 유기태양전지용 양극버퍼층 MoO3 박막의 물성 - 박재형; Jae Hyoung Park; 정기창; Ki Chang Jung; 문대화; Hyo Jung Bae; 배효정; Dae Hwa Mun; 이인우; In Woo Lee; 박성진; Jin Park; et al. (대한금속·재료학회지, 51(6), 2013)
Acidic PEDOT: PSS anode buffer layers (ABLs) are widely used for improving efficiency in organic based solar cells. Recently, stable p-type metal oxides, such as NiO, MoO3, and V2O5, have been used to replace the commonly used acidic PEDOT:PSS ABL. Among these metal oxides, the thermally evaporated MoO3 anode buffer layer is largely used because it has appropriate optical and electrical properties. In this study, we used rapid thermal annealing (RTA) for fabricating polycrystalline MoO3 thin films. MoO3 thin films were fabricated by annealing 30 nm molybdenum in an oxygen atmosphere under 350℃-550℃ RTA conditions at intervals of 100℃. In particular, we suggest an optimized temperature of 450℃ for efficient ABL in organic based solar cells. The MoO3 thin film with 450℃ RTA conditions has the relatively highest RMS roughness (46.5 nm) and proper electrical resistance. The characteristics of MoO3 ABLs fabricated by the RTA process of Mo are compared with thermally evaporated MoO3 ABL. (Received September 25, 2012).